The Impact of Time Spent on Social Media on the Occurrence of Anxiety in Youth: A Cross-Sectional Study in Surakarta, Indonesia - Aris Widiyanto; Joel Rey Ugsang Acob; France Allan M. Cavite; Tri Yuniarti; Joko Tri Atmojo (Journal of Nursing Practice)
Background: In the era of technology and globalization, social media with youth is something that cannot be separated. However, the surge of information shared easily and sometimes unverified through social media can triggers anxiety, especially among teenager who spent overwhelmingly hours with social media.